36=-1+7a

Simple and best practice solution for 36=-1+7a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=-1+7a equation:



36=-1+7a
We move all terms to the left:
36-(-1+7a)=0
We add all the numbers together, and all the variables
-(7a-1)+36=0
We get rid of parentheses
-7a+1+36=0
We add all the numbers together, and all the variables
-7a+37=0
We move all terms containing a to the left, all other terms to the right
-7a=-37
a=-37/-7
a=5+2/7

See similar equations:

| 11-12=-12+n | | 50t=0.25t+100 | | -1x+2-2x=-12-x | | 1.6=7.6-5(k+1.1 | | -2x+15=2x-5 | | 8x+3=8x+6 | | 2x+25=5(2x-3) | | 3+x+x2=0 | | y=-8/5(0)+4 | | x^2-169x-3600=0 | | (125x7.00)=150 | | -7x-3x=2=-8x-8 | | y=-8/5(8)+4 | | 4x-2(x-5)=-3+x+9 | | (125x700)=150 | | 4(+2)=x+10 | | 2=-8/5x+4 | | 6=-8/5x+4 | | 4n-2n=-11+n | | y=-8/5(3)+4 | | y=-8/5(2)+4 | | 3/4-x=2x | | -11-3y=34 | | x-8/5=x-12/9 | | y=-8/5(-1)+4 | | 42=3(-4a+6 | | 3(7x+8)=2x | | -8n+4n=-4(1+2n)-2(n+1) | | 7x–14=–28 | | -6(x=15) | | 3t+4.41=22.59 | | 233-2u=-21 |

Equations solver categories